Răspuns :
p+c=12 => p=12-c
3*p+4*c=43
Rezolvare:
3*(12-c)+4*c=43
36-3*c+4*c=43
c=7 => p=5
3*p+4*c=43
Rezolvare:
3*(12-c)+4*c=43
36-3*c+4*c=43
c=7 => p=5
1 pix + 1 caiet = 12 lei
1 pix = 12 lei - 1 caiet
3 x ( 12 + 1 caiet ) + 4 caiete = 43
36 - 3 caiete + 4 caiete = 43
1 caiet = 43 - 36 = 7 lei
1 pix + 7 lei = 12 lei
1 pix = 12 - 7 = 5 lei
proba: 1 x 5 + 1 x 7 = 12 lei
3 x 5 + 4 x 7 = 15 + 28 = 43 lei .
1 pix = 12 lei - 1 caiet
3 x ( 12 + 1 caiet ) + 4 caiete = 43
36 - 3 caiete + 4 caiete = 43
1 caiet = 43 - 36 = 7 lei
1 pix + 7 lei = 12 lei
1 pix = 12 - 7 = 5 lei
proba: 1 x 5 + 1 x 7 = 12 lei
3 x 5 + 4 x 7 = 15 + 28 = 43 lei .